Towards a sustainable development strategy for Buyukkonuk (Komi Kebir) village, Northern Cyprus - Oktay, D; Saymanlier, A; Ulucay, P; Ozgorun, A (Wit Press, 2003)
The concept of sustainability has come about as a result of increased levels of interest on economic viability that damaged the main components of the ecosystem and blocked its ability to sustain human values. Sustainable development is concerned with improvement of the quality of life of human beings - both at the urban and architectural levels - within the capacity of the global ecosystem. In fact, the idea of sustainability is not new; traditional planning and building methods were often good examples of sustainable design in their time, and represented good uses of local resources matched with local skills. In combination, they produced a built environment which met people's needs. Therefore, considering the fact that traditional settlements provide useful clues to achieve sustainable solutions in new developments, Buyukkonuk Village in Northern Cyprus has been selected as a case study to search for sustainability, as the-country is almost synonymous with its small-scale Mesourian villages. Our interest on the authentic olive oil mill from both community development and alternative tourism points of view has also made this decision more viable. Because, olive oil has come to symbolize the Mediterranean lifestyle and an olive oil press that used old stones to crush the olives is something that is unique for visitors to Cyprus to observe. However, due to the opening of a more modem and efficient mill nearby, Cypriot people are on the brink of losing it, like some other old mills in other villages. In line with these, this study outlines a framework to initiate a sustainable development strategy in Buyukkonuk based on the research undertaken and the survey conducted by the graduate students of Sustainable Developments course at the Faculty of Architecture of Eastern Mediterranean University. In this context, the following aspects will constitute the scope of the study: community development and rehabilitation of the olive oil mill, density and context, climatic aspects, open space and landscaping.
4th International Conference on Ecosystems and Sustainable Development -- JUN 04-06, 2003 -- SIENA, ITALY